LEGAL CONSEQUENCES OF CORRUPTION IN THE AL-QUR’ĀN; KHĀFĪ ALFĀZ APPROACH TO THE CORRUPTION VERSES - Basid, Abd.; Ashshiddiqi, Muhammad Naufal; Salsabila, Rif’atul Afifah; Sholiha, Dianatus (MUSHAF: Jurnal Tafsir Berwawasan Keindonesiaan, 2021)
The term corruption is known in modern society and was not found in the early days and development of Islam. In Indonesia, many corrupt practices were found around 1950. Furthermore, in relation to its legal arguments, al-Qur’an does not directly mention laws and sanctions for corruptors. Therefore there are many differences of opinion in determining the sentence. This research will discuss and explore the laws and sanctions for corruptors from the four verses of the Qur'an, namely QS. Āli ‘Imrān [3]: 161, QS. Al-Nisā '[4]: 29, QS. Al-Baqarah [2]: 188, and QS. Al-Māidah [5]: 38 using the khāfī alfāz interpretation approach. By using thematic methods and liberative hermeneutics, this study finds a conclusion that the law of corruption is the same as al-sāriq and the legal consequences are the same as thieves, namely punishment (cutting off hands) or imprisonment